If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 13 = 4 Reorder the terms: 13 + -3x = 4 Solving 13 + -3x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -3x = 4 + -13 Combine like terms: 13 + -13 = 0 0 + -3x = 4 + -13 -3x = 4 + -13 Combine like terms: 4 + -13 = -9 -3x = -9 Divide each side by '-3'. x = 3 Simplifying x = 3
| -3x-4=-4x-10 | | 2=5(x+9)+8x | | 5x-6=-x-30 | | (4z^6-2z^3+5)(z^3+27i)=0 | | -2x+18=-4x+34 | | 27/(-9) | | -9x+22+11x+21=2 | | 5cx-d=ax+b | | 5x+5=2x+23 | | 22t^4+18t^2-11t^6=0 | | -6=-2/3y | | 3x+18=-3x-6 | | 6n+11-8n=22 | | X^3-1/X^3=14 | | 7=8(x+5)+5 | | 3.4a=7.004 | | 1=1/3x^2 | | 5(11-3x)+4(2x+1)=3 | | 7(x+4)-(3x-1)=8 | | (3x+4)=5x | | y=ctg(1-2x) | | y=ctg(1-2xz) | | 2+2+3=3 | | (12x+20)+(7x)+(20x-35)=180 | | 6=6(x+5)-2x | | (3x+7)=(5x-3) | | 14=x*26 | | 2(x+7)+6=26 | | (5x-1)=(6x-3) | | 2=5(x+9)8x | | T=p-ir | | 4a^2-147=a^2 |